Continuous Renal Replacement Therapy in Pediatric Patients With Acute Kidney Injury After Liver Transplantation - Yan Sun; Yan Sun; Sinan Gao; Sinan Gao; Xingqiang Wang; Xingqiang Wang; Lixin Yu; Lixin Yu; Min Xu; Min Xu; Wei Gao; Wei Gao; et al. (Frontiers Media S.A., 2022)
ObjectiveThis study aimed to explore the clinical application of continuous renal replacement therapy (CRRT) in pediatric patients with acute kidney injury (AKI) after liver transplantation.MethodsPediatric patients who underwent liver transplantation were retrospectively investigated. Those who developed AKI within 1 year after the surgery were included and divided into a CRRT group and a non-CRRT group. The perioperative conditions and postoperative complications of the two groups were compared along with the prognoses of the groups to analyze the high-risk factors of the postoperative CRRT.Results189 (36.91%) patients developed AKI within 1 year after the liver transplantation surgery. There were 18 patients in the CRRT group and 171 in the non-CRRT group. The differences in the preoperative conditions were not statistically significant between the two groups. Compared with the non-CRRT group, patients in the CRRT group had significantly longer transplantation times, higher volumes of intraoperative hemorrhage, and increased incidence of postoperative unscheduled surgery, postoperative primary nonfunction of the transplanted liver, secondary liver transplantation, hepatic artery occlusion, and intestinal fistula (P < 0.05). Moreover, the proportion of patients in AKI stage 3 is higher in the CRRT group (83.33%) than that in the non-CRRT group (11.11%), P < 0.001. The median time to initiate CRRT was 10 days postoperatively, the median number of CRRT treatments per patient was 2 times, the average duration of each CRRT treatment was 10.1 h, and the average rate of the decrease in blood creatinine per treatment was 25.6%. Results of multivariate logistic regression analysis showed that AKI stage 3 [OR=40.000, 95%CI (10.598, 150.969), P = 0.016], postoperative unscheduled surgery [OR=6.269, 95%CI (3.051, 26.379), P = 0.007], and hepatic artery occlusion [OR = 17.682, 95%CI (1.707, 40.843), P = 0.001] were recognized as risk factors for postoperative AKI with CRRT therapy. The one- and two-year survival rates were 72.22% and 72.22% in the CRRT group, respectively; and 97.08% and 96.49% in the non-CRRT group, accordingly. There were statistically significant differences in the one- and two-year survival rates between the two groups (P < 0.001).ConclusionThe incidence of AKI after liver transplantation in pediatric patients was high. Patients with AKI stage 3, hepatic artery occlusion, and underwent unscheduled surgery postoperatively were with a high likelihood of receiving CRRT, which was related to a lower one- and two-year survival rates. CRRT effectively improved the one- and two-year survival rates.